THE INFLUENCE OF SERVICE QUALITY, COMPANY IMAGE AND SWITCHING BARRIER THROUGH CUSTOMER SATISFACTION ON CUSTOMER RETENTION - Muhammad Maladi; Nazief Nirwanto; Achmad Firdiansjah (AIBPM Publisher, 2019)
This study aims to analyze the effect of service quality, company image, switching barriers on customer retention through customer satisfaction at LB-LIA Banjarmasin. The results revealed that service quality has significant effects on customer satisfaction and customer retention, corporate image has an effect on customer satisfaction while switching barriers do not significantly influence customer satisfaction or customer retention and lastly customer satisfaction has a significant effect on customer retention. It is recommended that service quality should be maintained.